2017
DOI: 10.3233/wor-172608
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of safe patient handling and mobilization programs: A meta-analysis

Abstract: Objective: We performed a systematic meta-analysis of safe patient handling and mobilization (SPHM) program evaluations. Methods: Systematic literature review identified published SPHM program evaluations. Injury Rate Ratios (IRR), pre- to post-intervention, were used to estimate intervention effects and to examine the influence of patient care level, program components, and follow-up time using meta-regression. Results: 27 articles reported evaluations from 44 sites. Combined effect estimate for all SPHM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 45 publications
1
19
1
2
Order By: Relevance
“…Musculoskeletal injury risk also showed a decreasing pattern although the finding was not significant. Many institutional‐level intervention studies have reported positive effects of SPH programs on musculoskeletal injury reduction . In our study, risk reduction was not observed for minor symptom parameters.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Musculoskeletal injury risk also showed a decreasing pattern although the finding was not significant. Many institutional‐level intervention studies have reported positive effects of SPH programs on musculoskeletal injury reduction . In our study, risk reduction was not observed for minor symptom parameters.…”
Section: Discussioncontrasting
confidence: 63%
“…Following the implementation of these standards, evaluation research is needed to assess the impact and effectiveness of the SPH law on hospital programs and practices and musculoskeletal injury prevention. While there are reports of positive outcomes of SPH programs at a single hospital or health systems level, limited data exist on the statewide impact of SPH legislation. Only Washington State evaluated the impact of SPH legislation and reported reduction of workers’ compensation claim rates from musculoskeletal disorders …”
Section: Introductionmentioning
confidence: 99%
“…Previous findings have suggested that participation in an SPHM training program decreased risk of patient care worker injuries. 3 Consistent with these findings, in the present study, several participants were able to immediately apply the knowledge gained from the training in their home caregiving duties to decrease risk of personal injury.…”
Section: Discussionsupporting
confidence: 86%
“…Evidence shows that SPHM programs have been highly effective in reducing patient care worker injuries. 3 Implementation of SPHM programs for in-home nonmedical and family caregivers has been more challenging. Programs designed to protect home caregivers from injury could be even more critical as these caregivers may be the patient's only resource for home care.…”
Section: Introductionmentioning
confidence: 99%
“…The PubMed search strategy is available as an online supplement (see the Supplementary Materials Table S1 ). Reference lists of the included studies and key articles [ 37 , 38 , 39 , 40 , 41 , 42 ] were examined for further studies. Studies in all languages were included.…”
Section: Methodsmentioning
confidence: 99%